2004
DOI: 10.1152/ajpgi.00184.2004
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ/STAT1 acts as a proinflammatory signal in T cell-mediated hepatitis via induction of multiple chemokines and adhesion molecules: a critical role of IRF-1

Abstract: We have previously shown that IFN-gamma/STAT1 plays an essential role in concanavalin A (ConA)-induced T cell hepatitis via activation of apoptotic signaling pathways. Here we demonstrate that IFN-gamma/STAT1 also plays a crucial role in leukocyte infiltration into the liver in T cell hepatitis. After injection of ConA, leukocytes were significantly infiltrated into the liver, which was suppressed in IFN-gamma(-/-) and STAT1(-/-) mice. Disruption of the IFN regulatory factor-1 (IRF-1) gene, a downstream target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
136
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 57 publications
6
136
1
1
Order By: Relevance
“…We identified hepatocytes and LSECs as CXCR3 ligand-producing cells upon Con A challenge in vivo and thus demonstrated their involvement in CXCR3 + lymphocyte recruitment. In this context, Jaruga et al (16) reported that IFN-g treatment induces the expression of several chemokines in primary hepatocytes, LSECs, and Kupffer cells through activation of STAT1, STAT3, and IFN regulatory factor 1. Accordingly, the lack of IFN regulatory factor 1 resulted in protection against Con A-induced hepatitis due to suppressed chemokine expression (among others, CXCL9, CXCL10, and CXCL11) and decreased leukocyte infiltration into the liver (16).…”
Section: Discussionmentioning
confidence: 99%
“…We identified hepatocytes and LSECs as CXCR3 ligand-producing cells upon Con A challenge in vivo and thus demonstrated their involvement in CXCR3 + lymphocyte recruitment. In this context, Jaruga et al (16) reported that IFN-g treatment induces the expression of several chemokines in primary hepatocytes, LSECs, and Kupffer cells through activation of STAT1, STAT3, and IFN regulatory factor 1. Accordingly, the lack of IFN regulatory factor 1 resulted in protection against Con A-induced hepatitis due to suppressed chemokine expression (among others, CXCL9, CXCL10, and CXCL11) and decreased leukocyte infiltration into the liver (16).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that NK cells were the effectors to mediate the over-sensitive liver injury in an IFN-c-dependent manner in HBsAg transgenic mice. As demonstrated in ConA-induced hepatitis or LPS/D-galactosamineinduced liver damage, IFN-c plays an important role in the development of hepatic inflammation and liver injury through induction of chemokines, adhesive molecules, and proapoptotic proteins by activation of STAT1 [29,[43][44][45][46]. We observed higher expressions of IFN-c receptor on hepatocytes of HBsAg transgenic mice and stronger IFN-c signaling of pSTAT1-IRF-1, which might account for the hypersensitivity to IFN-cinduced hepatocyte injury in HBsAg transgenic mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation and culture of primary mouse hepatocytes were performed as described [29]. Followed by treatment with IFN-c for various time periods, downstream signals of hepatocytes were determined by Western blotting.…”
Section: Isolation and Culture Of Primary Mouse Hepatocytesmentioning
confidence: 99%
“…IFN-g-deficient mice (14) or mice treated with an IFN-gneutralizing Ab (12,21) show resistance to Con A-induced hepatic injury, as the IFN-g/STAT1/IRF-1 pathway is crucial for leukocyte infiltration and the expression of multiple cytokines, chemokines, and adhesive molecules (24). Consistent with these findings, we confirmed that Con A hepatic injury was attenuated in Ifngr1 2/2 mice, suggesting the important role of IFN-g signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that mice deficient in IFN-g and STAT1 are resistant to Con A-induced hepatic injury (14,22,23). IFN-g stimulation activates hepatocytes, sinusoidal endothelium, and Kupffer cells through a STAT1-dependent pathway to produce chemokines, including monokine induced by IFN-g, CCL-20, ENA-78 (epithelial cell-derived neutrophil-activating peptide), and adhesion molecules such as intracellular adhesion molecule-1 (CD54) and VCAM-1 (CD106), which may promote leukocyte infiltration into the liver (24). Additionally, treatment with IFN-g causes upregulation of CD95 in hepatocytes, followed by NKT-derived, CD95 ligand/CD95-mediated hepatic cell death and Con A-induced hepatic injury (14,(25)(26)(27)(28).…”
mentioning
confidence: 99%